Analysis of the Regulatory Effect of ACTG2 on Biological Behavior of Bladder Cancer Cells Based on Database Screening: Analysis of the role of ACTG2 in bladder cancer - Liu, Hailong; Xiang, Ping; Miao, Wenhao; Liu, Haitao; Shen, Haibo; Xue, Song (Cellular and Molecular Biology, 2023)
To identify genes aberrantly expressed in bladder cancer (BC) in the GEO dataset GSE 52519, and analyze the impact of abnormal Actin Gamma 2, Smooth Muscle (ACTG2) expression on BC cells. GSE 52519, a public dataset in the Gene expression omnibus (GEO) database, was selected for differential expression analysis. Differentially expressed ACTG2 vectors were selected to construct the aberrant expression vectors and transfected into BC T24 and J82 cells. The influences of ACTG2 on BC cell biological behavior were determined by cell cloning, Transwell and flow cytometry, and alterations in cell cycle status were observed. A total of 166 DEGs were found in the GSE 52519 dataset, among which ACTG2 was abnormally low in expression. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses identified that the keywords involved mainly included “extracellular region”, “cytoskeleton”, “Vascular smooth muscle contraction”, “IL-17 signaling pathway”, etc. Further, through online data analysis, ACTG2 was also found to be under-expressed in neoplastic diseases such as bladder urothelial carcinoma (BLCA) and prostate adenocarcinoma (PRAD). In vitro, ACTG2 presented lower expression in T24 and J82 than in SV-HUC-1 (P<0.05). Enhanced capacities to proliferate and invade and reduced apoptosis of T24 and J82 were found after silencing ACTG2 expression, with shortened G0-G1 phase and prolonged S phase (P<0.05). However, overexpressing ACTG2 came with decreased BC cell activity, enhanced apoptosis, as well as prolonged G0-G1 phase and shortened S phase (P<0.05). In conclusion, low expression of ACTG2 in BC can shorten the G0-G1 phase of BC cells, prolong the S-phase.